2013
DOI: 10.1002/aoc.2990
|View full text |Cite
|
Sign up to set email alerts
|

CuI/amino acid‐catalyzed coupling and cyclization of β‐bromo‐α,β‐unsaturated amides with terminal alkynes leading to (3Z)‐3‐alkylidenepyrrol‐1‐ones

Abstract: CuI/amino acid-catalyzed coupling and cyclization of b-bromo-a,b-unsaturated amides with terminal alkynes leading to (3Z)-3-alkylidenepyrrol-1-ones b-Bromo-a,b-unsaturated amides are coupled and cyclized with terminal alkynes in DMF at 110 C in the presence of a catalytic amount of CuI and amino acid along with a base to give the corresponding (3Z)-3-alkylidenepyrrol-1-ones in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The isolation of pure products was carried out via thin layer (silica gel 60 GF 254 , Merck) chromatography. The starting β‐bromo‐α,β‐unsaturated amides were synthesized via three steps from the corresponding ketones according to literature procedures, and all are known . Commercially available organic and inorganic compounds were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of pure products was carried out via thin layer (silica gel 60 GF 254 , Merck) chromatography. The starting β‐bromo‐α,β‐unsaturated amides were synthesized via three steps from the corresponding ketones according to literature procedures, and all are known . Commercially available organic and inorganic compounds were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, such scaffold‐containing compounds have been synthesized and tested for biological activity. During the course of our continuing studies directed towards transition metal‐catalyzed cyclization reactions of β‐bromo‐α,β‐unsaturated aldehydes and their derivatives, we have identified several new methods for the synthesis of carbocyclic and heterocyclic compounds . β‐Bromo‐α,β‐unsaturated aldehydes and their derivatives are readily prepared from α‐methylene group‐containing ketones by bromination under Vilsmeier–Haack conditions and subsequent transformation, and the products can serve as valuable building blocks for the construction of various cyclic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Sonogashira coupling reactions are some of the most important methods to furnish arylalkynes or conjugated enynes, which have been used as key precursors for the syntheses of natural products, pharmaceuticals as well as organic materials . Particularly, palladium complexes are the most commonly used catalysts for such transformations, mostly due to their remarkable catalytic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] β-Bromo-α,β-unsaturated aldehydes and their derivatives are readily prepared from α-methylene group-containing ketones by bromination under Vilsmeier-Haack conditions [20,21] and subsequent transformation, and the products can serve as valuable building blocks for the construction of various cyclic compounds. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Among such carbonlative cyclization reactions, we recently have shown that β-bromo-α,β-unsaturated carboxylic acids can be carbonylatively cyclized with 2,2-dimethylhydrazine under carbon monoxide pressure in the presence of a palladium catalyst to give 1-(dimethylamino)-1H-pyrrole-2,5-diones. [39] The present work arose during the course of the application of this protocol to the reaction with arylhydrazines.…”
Section: Introductionmentioning
confidence: 99%